Hyaluronan delivery by polymer demixing in polysaccharide-based hydrogels and membranes for biomedical applications. (5th October 2016) - Travan, Andrea; Scognamiglio, Francesca; Borgogna, Massimiliano; Marsich, Eleonora; Donati, Ivan; Tarusha, Lorena; Grassi, Mario; Paoletti, Sergio
Highlights: Alginate-hyaluronan hydrogels were obtained exploiting a polymer demixing process. Freeze-dried membranes with tunable mechanical properties were manufactured. Hyaluronan released from membranes stimulates fibroblasts migration/proliferation. The molecular arrangement of hyaluronan favors its in situ release. Abstract: Alginate-based membranes containing hyaluronic acid (HA) were manufactured by freeze-drying calcium-reticulated hydrogels. The study of the distribution of the two macromolecules within the hydrogel enabled to highlight a polymer demixing mechanism that tends to segregate HA in the external parts of the constructs. Resistance and pliability of the membranes were tuned, while release and degradation studies enabled to quantify the diffusion of both polysaccharides in physiological solution and to measure the viable lifetime of the membranes. Biological studies in vitro proved that the liquid extracts from the HA-containing membranes stimulate wound healing and that fibroblasts are able to colonize the membranes. Overall, such novel alginate-HA membranes represent a promising solution for several medical needs, in particular for wound treatment, giving the possibility to provide an in situ administration of HA from a resorbable device.